Tribal Water Rights : Essays in Contemporary Law, Policy, and Economics - Colby, Bonnie G.; Britton, Sarah, 1976-; Thorson, John E. (Book collections on Project MUSE., 2006)
Fourteen contributions from academics and legal practitioners explore some of the complex issues that arise in negotiating and implementing Indian water rights settlements, and including such topics as tribal jurisdiction over water quality; the special case of pueblo water claims; and the tribal management of hydropower facilities. In the final chapter, the editors consider the significance of the work of tribal activists.